THE INFLUENCE OF LIQUIDITY, SOLVENCY, PROFITABILITY, AND COMPANY SIZE ON STOCK PRICES - Afrilia Nola Hestiatay; zaky Machmuddah; Natalistya TAH (Dinamika Akuntansi Keuangan dan Perbankan, 2023)
Providing empirical evidence regarding liquidity, solvency, profitability, firm size on stock prices is the purpose of this research. Secondary data through the collection of financial statements of energy companies for 2017-2021 obtained through the official website of the Indonesia Stock Exchange (www.idx.co.id) and the Indonesia Finance Market (www.finance.yahoo.com) are data used in research. Using data in the form of company financial statements and company stock prices. The sampling technique used was purposive sampling. Path analysis with WarpPLS 7.0 software as the analysis tool is applied. With the results of the observation is the effect of liquidity, profitability, and company size with stock prices, however, solvency has no effect on stock prices.